Short-term results of the management of severe bone defects in primary TKA with cement and K-wires - Muhammet Sadik Bilgen; Gokay Eken; Nejat Guney (Acta Orthopaedica et Traumatologica Turcica, 2017)
Objective: The aim of this study was to evaluate the results of cement and kirschner wire augmentation in the management of bone defects in primary TKA. Methods: Twenty-four patients (10 male, 14 female; mean age: 66 years) with uncontained unilateral medial tibial articular bone defect who underwent TKA between 2010 and 2014 were included in this study. The average follow up time was 33.7 months. Patients were divided to two groups according to the size of the bone defect (Group 1: <20 mm, Group 2: >20 mm). The tibial defect was reconstructed by using cement and K-wires. We used posterior stabilized prosthesis with no tibial stem extension. Results: The preoperative and postoperative lower extremity mechanical axis in Group I was in a mean varus of 15° and mean varus of 3°, respectively (p < 0.001). The preoperative and postoperative lower extremity mechanical axis in Group 2 was in a mean varus of 20° and mean varus of 3° respectively in Group II (p < 0.001). None of the patients neither suffered from failure of K-wires nor loosening. Conclusion: The use of cement and K-wires augmentation appears to be a simple and cost-effective treatment option for the tibial bone defects in primary TKA. Level of evidence: Level IV, Therapeutic study. Keywords: Bone defect, Bone cement, Kirschner wire, Total knee arthroplasty